Peripheral T-cell lymphoma – are we making progress?. Issue 3 (September 2018) - Khan, Niloufer; Ozkaya, Neval; Moskowitz, Alison; Dogan, Ahmet; Horwitz, Steven
Abstract: Peripheral T cell lymphoma (PTCL) is a rare subtype of non-Hodgkin lymphoma. PTCLs are heterogeneous in terms of biology, but generally have more aggressive features and poorer outcomes than aggressive B-cell lymphomas when treated with combination chemotherapy. While the best long-term results are still seen with intensive chemotherapeutic approaches, significant progress has been made with molecular profiling identifying genetic drivers of PTCL that could serve as therapeutic targets. Tailoring therapy to different subtypes of PTCL may lead to more individualized approaches with the hope of improved outcomes. In this paper, we review current therapies for treatment of PTCL, newly identified molecular markers, and the role of emerging therapy and novel combinations of existing agents.